Dampak gangguan kecemasan pada kesehatan mental dan kualitas hidup: Perspektif klinis - Mufidah, Alvia Lailatul (Maliki Interdisciplinary Journal, 2025)
Anxiety disorders can have significant impacts on an individual's mental health and quality of life. This literature review aims to explore the clinical perspective of the impacts of anxiety disorders on mental health and quality of life. Anxiety disorders can cause emotional impacts such as excessive worry and fear, social anxiety, hopelessness, frustration, and depression. These emotional impacts can affect an individual's mental and physical well-being. Anxiety disorders can also cause physical impacts such as an increased risk of cardiovascular disease, digestive problems, weakened immune system, and disruption of the central nervous system and cardiovascular system. Cognitive impacts of anxiety disorders include cognitive impairment, cognitive distortion, attention control disorder, and low social competence. Cognitive-behavioral therapy can help reduce anxiety symptoms by replacing negative thoughts with positive ones. In addition, doctors may prescribe antidepressants to help modify an individual's brain chemistry. It is important to manage anxiety disorders properly to prevent negative impacts on an individual's mental and physical health.